Single Alkali Metal Ion-Activated Porous Carbon With Heteroatom Doping for Supercapacitor Electrode - Wang, Changshui (Frontiers in Chemistry, 2020)
A single alkali metal ion activation method was employed to prepare sulfur-doped microporous carbons. A series of alkali metal ions such as Li+, Na+, K+ and Cs+ were employed in the polymerization process of 3-hydroxythiophenol and formaldehyde to obtain metal ion anchored sulfur-containing resin, which was further treated to obtain xerogel and carbonized to obtain microporous carbon with sulfur doping. In this case, the monodispersed alkali metal ions could realize highly effective activation with low activating agent dosage. Intensive material characterizations show that the pore structure and surface properties of as-prepared carbons are determined by the alkali metal ions. C-Cs prepared by Cs+ ion possesses a high Brunauer-Emmett-Teller specific surface area of 1037 m2 g-1 with interconnected microporosity and sulfur doping. The specific capacitance of C-Cs can reach up to 270.9 F g-1 in a two-cell electrode measurement system while C-Cs based supercapacitor can delivered an energy density of 7.6 Wh kg-1, which is much larger than that of other samples due to its surface functionalities and well-interconnected porosities.